1983
DOI: 10.1007/bf02679785
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of 2‐pentenylfurans in the reversion flavor of soybean oil

Abstract: The volatile flavor compounds in a reverted soybean oil with a peroxide number of 6.0 meq/kg were isolated by semicontinuous countercurrent vacuum steam distillation. Based upon the gas Chromatographic retention times and mass spectra of the four synthesized 2‐pentenylfurans, it was found that cis‐ and trans‐2‐(l‐pentenyl)furans and a mixture of cis‐ and trans‐2‐(2‐pentenyl)‐furans are present in reverted soybean oil. At least the greater portion of 2‐(2‐pentenyl)furans identified was cis‐isomer. These compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…There is however another possible pathway for the production of furans, which has never been suggested in dairy products, i.e. the oxidation of polyunsaturated fatty acids [17]. In our study, the total amount of furans in cheese was correlated with the proportion of polyunsaturated fatty acids in the milk (R 2 = 0.62, P < 0.001).…”
Section: Volatile Compounds In Cheesesupporting
confidence: 38%
“…There is however another possible pathway for the production of furans, which has never been suggested in dairy products, i.e. the oxidation of polyunsaturated fatty acids [17]. In our study, the total amount of furans in cheese was correlated with the proportion of polyunsaturated fatty acids in the milk (R 2 = 0.62, P < 0.001).…”
Section: Volatile Compounds In Cheesesupporting
confidence: 38%
“…A beany flavor, which is a unique and undesirable flavor in soybean oil with low peroxide value, has been a problem for the last 70 years and studied extensively both nationally and internationally (Chang and others 1966; Smouse and Chang 1967). 2‐Pentylfuran and pentenylfuran were reported to be responsible for the beany flavor (Chang and others 1966, 1983; Smouse and Chang 1967; Ho and others 1978; Smagula and others 1979), and 1 O 2 was involved in their formation from linoleic and linolenic acids present in soybean oil, as shown in Figure 9 and 10 (Min and others 2003). Min and others (2003) strongly indicated that the reversion flavor of soybean oil can be decreased or eliminated by removing chlorophylls from the oil during processing.…”
Section: Singlet Oxygen Formation and Mechanisms Of Photosensitized Omentioning
confidence: 99%
“…At concentration levels of 1-10 mg/kg these compounds impart characteristic beany, grassy, metallic, liquorice and buttery flavours to various oils (Table 6.3). Chang et al (1966) suggested the fonnation of 2-pentylfuran from 4-ketononanal, possibly derived from oxidised linoleic acid:…”
Section: Furansmentioning
confidence: 99%